2013
DOI: 10.1055/s-0032-1333232
|View full text |Cite
|
Sign up to set email alerts
|

Macroprolactinemia in Patients with Prolactinomas: Prevalence and Clinical Significance

Abstract: In few cases, the presence of typical hyperprolactinemia-related clinical symptoms and their disappearance after treatment with DA suggests biological activity of macroprolactin comparable with that of monomeric prolactin isoform. Decrease of macroprolactin levels after DA treatment could suggest tumoral origin of the high-molecular isoform in these rare cases. Although macroprolactinemia is considered a benign condition, pituitary imaging, DA treatment, and prolonged follow-up may be necessary in certain case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The prevalence of macroprolactinemia among newly diagnosed prolactinoma patients is similar compared with the control group of healthy subjects (3.5 vs. 3.7%), and may be explained by the coexistence of a pituitary adenoma and macroprolactinemia or macroprolactin production by the pituitary tumour itself [12].…”
Section: Diagnosismentioning
confidence: 74%
See 3 more Smart Citations
“…The prevalence of macroprolactinemia among newly diagnosed prolactinoma patients is similar compared with the control group of healthy subjects (3.5 vs. 3.7%), and may be explained by the coexistence of a pituitary adenoma and macroprolactinemia or macroprolactin production by the pituitary tumour itself [12].…”
Section: Diagnosismentioning
confidence: 74%
“…However, macroprolactinemia may be more common, with a recently reported prevalence of 3.7% and no difference in prevalence between genders [14]. Because the reported proportion of macroprolactinemia in hyperprolactinemic populations is much higher in most studies and varies between 15 and 35% (mean prevalence 25%), macroprolactinemia is therefore considered a common finding in endocrinological practice [3,8,12,13]. One study reported a prevalence of 46%, but it is likely that this particular incidence reflected selection bias because of the specialized nature of the study center, which received samples sent from other laboratories when the possible diagnosis of macroprolactinemia was raised [15].…”
Section: Prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…In this context, macroprolactinemia association with pituitary adenomas requires special attention (67,68), especially if PRL levels remain elevated after PEG precipitation (Figure 3) (1,4,65). However, the prevalence of macroprolactinemia did not differ in patients with prolactinomas and in the control group (3.5% vs. 3.7%; p = 1.00) in a recent study (69). Macroprolactinemia was recently reported in 5.8% of women with PCOS (70).…”
Section: Clinical Relevancementioning
confidence: 89%